Socialists and communists and the Catalan national question: From 1888 until recent times - Albert Balcells (Catalan Historical Review)
During the first third of the twentieth century, the socialists did not have a positive stance towards the Catalan demand for autonomy, and the dependence on the socialist leadership in Madrid hindered their expansion in Catalonia, where anarcho-syndicalism predominated until 1936. After the unification of socialists and communists in Catalonia at the beginning of the Civil War, the unified party and its trade union became a central force until the republican defeat in 1939. After the Franco regime, socialism became an important force in Catalonia until it started to govern the Generalitat in 2003 and contributed to the re-Catalanisation of the country.